Allosteric Control of Substrate Specificity of the Escherichia coli ADP-Glucose Pyrophosphorylase - Ebrecht, Ana C.; Solamen, Ligin; Hill, Benjamin L.; Iglesias, Alberto A.; Olsen, Kenneth W.; Ballicora, Miguel A. (Frontiers in Chemistry, 2017)
The substrate specificity of enzymes is crucial to control the fate of metabolites to different pathways. However, there is growing evidence that many enzymes can catalyze alternative reactions. This promiscuous behavior has important implications in protein evolution and the acquisition of new functions. The question is how the undesirable outcomes of in vivo promiscuity can be prevented. ADP-glucose pyrophosphorylase from Escherichia coli is an example of an enzyme that needs to select the correct substrate from a broad spectrum of alternatives. This selection will guide the flow of carbohydrate metabolism towards the synthesis of reserve polysaccharides. Here, we show that the allosteric activator fructose-1,6-bisphosphate plays a role in such selection by increasing the catalytic efficiency of the enzyme towards the use of ATP rather than other nucleotides. In the presence of fructose-1,6-bisphosphate, the kcat/S0.5 for ATP was near ~600-fold higher that other nucleotides, whereas in the absence of activator was only ~3-fold higher. We propose that the allosteric regulation of certain enzymes is an evolutionary mechanism of adaptation for the selection of specific substrates.